The effect of the use of melatonin in the treatment of intestinal inflammatory diseases: an integrative review (Research, Society and Development, 2019)
Inflammatory Bowel Diseases (IBD) is characterized by inflammation of the gastrointestinal tract and the two most common types are Crohn's disease (DC) and ulcerative colitis (UC). Both diseases have relapsing immune function. In the extreme context, a melatonin (LMT), is triggered enzymatically from L-tryptophan, has been shown to be a versatile hormone favorable in the treatment of DII disease. Based on the main complications associated with an IBD, the objective of this review is to integrate the decision-making of the main clinical actors related to the use of MLT in the treatment of Crohn's disease (DC) and ulcerative colitis (RCU). For that, an integrative review was performed considering the bibliographies selected in the main databases. The MLT appears to play a significant role in GIT, with no gastrointestinal side effects, with free radical effects, local anti-inflammatory activity, and a moderation of visceral. Thus, it appears to be a promising alternative in the treatment of IBD.